Dental Desmineralization: “In vitro” Evaluation of Pediatric Corticosteroids (Research, Society and Development, 2025)
Dental erosion is a chemical process that results in the irreversible loss of tooth enamel structure, often intensified by the frequent consumption of acidic substances. In children, liquid medications, especially pediatric corticosteroids, are widely used and usually contain sweeteners and acidifiers, which can compromise oral health. The present study aimed to evaluate the erosive and cariogenic potential of pediatric corticosteroid-based medications, based on the analysis of pH and Brix degree of different formulations available on the market. Six liquid medications were selected, divided into two main groups: three based on prednisolone and three containing the combination of betamethasone with dexchlorpheniramine maleate. The analysis was performed using a digital pH meter and refractometer, using controlled temperature and standardized methodology. The results revealed significant differences between the groups analyzed. It is concluded that the formulations analyzed, especially those containing betamethasone, represent a potential risk to the dental structure of children, especially in the deciduous dentition, which is more vulnerable to demineralization. Thus, this study reinforces the importance of guiding parents and guardians regarding oral hygiene after using liquid medications. Furthermore, it is suggested that the pharmaceutical industry invest in less harmful alternatives to oral health, such as replacing sucrose with non-fermentable sweeteners and using buffer systems to control pH. Preventive dentistry should consider these aspects in pediatric care, promoting integrated actions between health professionals and manufacturers.